Inhibition Effects of Jakarta Bay Sediments to the Growth of Marine Diatom (Chaetoceros Gracilis) - Triyoni Purbonegoro; Muhammad Reza Cordova; Rachma Puspitasari; Dwi Hindarti (BULLETIN OF THE MARINE GEOLOGY, 2018)
Jakarta Bay coastal ecosystem is known suffered from water pollution and habitat degradation. Solid and fluid waste from households and several industrial areas flow and ended up in the bay. Ecotoxicological studies are needed to assess the effects of pollutant on marine organism, including phytoplankton as the primary producer. Therefore chemical analysis and toxicity test were performed to investigate the impact of Jakarta Bay Sediments to marine diatoms Chaetoceros gracilis. Heavy metals concentration especially Cu, Pb, Cd, and Hg in the sediments were lower than in previous studies. It could be related to the stricter environmental regulations which started enforced at the end of 1990s. Meanwhile, PAH and pesticide were higher than in previous studies. Increasing activities and maritime traffic in surrounding area of Tanjung Priok Port area and most likely comes from other adjacent harbors (Muara Baru, Muara Angke, and Marina Ancol harbor) and the massive usage of the pesticide compound in the households of the Jakarta City area were suspected to be the reasons. Estuaries area and locations <10 km were identified and predicted would produce harmful effects since the concentration of Zn and Hg in those area exceeded Probable Effects Level (PEL) of Sediment Quality Guidelines (SQG). The growth responses of Chaetoceros gracilis were varied greatly. Most of the sites (24 from 31 sites) showed inhibition effects on the growth of diatoms, ranged from 1.75-35.33 % (17.75±9.59 %) relative to control, with the highest inhibition value was at Cengkareng Drain estuary (M2). The relationship between the concentration of contaminants and the inhibition response could not be clearly explained, however, there is an assumption that low concentrations of some heavy metals were suspected to give adverse effects on diatom’s growth.Keywords: sediment, toxicity, marine diatoms, Chaetoceros gracilis, Jakarta BayEkosistem Teluk Jakarta dikenal mengalami pencemaran air dan degradasi habitat. Limbah cair dan padat berasal dari perumahan dan industri mengalir dan berakhir di teluk tersebut. Kajian ekotoksikologi diperlukan untuk mengetahui pengaruh pencemar terhadap organisme laut termasuk fitoplankton sebagai produsen primer. Analisis kimia dan uji toksisitas dilakukan untuk mengetahui dampak sedimen Teluk Jakarta terhadap diatom laut Chaetoceros gracilis. Konsentrasi logam berat terutama Cu, Pb, Cd, dan Hg dalam sedimen lebih rendah dari penelitian sebelumnya. Hal tersebut berkaitan dengan peraturan lingkungan ketat yang mulai diberlakukan pada akhir 1990-an. Namun demikian, konsentrasi PAH dan pestisida lebih tinggi dari penelitian sebelumnya. Hal tersebut diduga kuat akibat dari peningkatan aktivitas dan lalu lintas maritim di daerah sekitar Pelabuhan Tanjung Priok, juga kemungkinan besar berasal dari pelabuhan lain yang berdekatan (Muara Baru, Muara Angke, dan pelabuhan Marina Ancol) serta akibat penggunaan besar-besaran senyawa pestisida kegiatan rumah tangga di wilayah Kota Jakarta. Daerah dan lokasi estuaria <10 km diidentifikasi dan diprediksi akan menghasilkan efek berbahaya karena konsentrasi Zn dan Hg di area tersebut melebihi Probable Effects Level (PEL) dari Pedoman Kualitas Sedimen (SQG). Respon pertumbuhan diatom laut Chaetoceros gracilis sangat bervariasi. Sebagian besar stasiun (24 dari 31 stasiun) menunjukkan efek penghambatan pada pertumbuhan diatom, berkisar antara 1,75-35,33% (17,75 ± 9,59%) relatif terhadap kontrol, dengan nilai penghambatan tertinggi di muara Sungai Cengkareng (M2). Hubungan antara konsentrasi kontaminan dan respon penghambatan tidak dapat dijelaskan dengan lebih pasti namun terdapat asumsi konsentrasi rendah dari beberapa logam berat diduga memberikan efek buruk pada pertumbuhan diatom.Kata Kunci: sedimen, toksisitas, diatom laut, Chaetoceros gracilis, Teluk Jakarta